Effect of Aged Cherry Orchard Soil on the Potted Seedling Growth of Malus hupehensis (Pamp.) Rehd - Lei Qin; Xiaoxuan Li; Weitao Jiang; Yusong Liu; Chengmiao Yin; Zhiquan Mao (Horticulturae, 2024)
Due to the aging of trees, aged apple and cherry orchards need to be rebuilt urgently. However, due to the limitation of land resources, it is inevitable to rebuild the apple orchard by taking the aged cherry orchard as a replacement, which will lead to replant disease and seriously affect the sustainable development of the horticulture industry. This study investigated the effect of aged cherry orchard soil on the growth of M. hupehensis seedlings grown in pots, and it was further verified that allelochemicals in soil were one of the reasons for this effect. Three treatments were implemented: aged apple orchard soil (ppl), aged cherry orchard soil (pyl), and aged cherry orchard soil after fumigation with methyl bromide (pyz). Compared with pyz, pyl treatment significantly decreased the biomass, root growth, and antioxidant enzyme activity of M. hupehensis seedlings, and increased the content of MDA. Compared with ppl, pyl contains a smaller number of fungi and bacteria, but the abundance of the four disease-causing Fusarium remained high. In addition, the levels of allelochemicals found in the soil of aged cherry orchards can inhibit the normal growth and development of M. hupehensis seedlings. Amygdalin most strongly inhibited these seedlings. In summary, directly planting M. hupehensis seedlings in the soil of the aged cherry orchards still inhibits their normal growth and development, although the seedlings grow better than in aged apple orchard soil. Therefore, it is not feasible to directly plant M. hupehensis seedlings in the soil of aged cherry orchards, and measures should be taken to eliminate allelochemicals such as amygdalin and harmful microorganisms.